Dinâmica dos atropelamentos de fauna em uma região de floresta subtropical no sul do Brasil - Deffaci, Ângela Camila Grando (2015)
Roads are among the most obvious environmental changes generated by man. One of the most noticeable impact is death by run over of fauna that can cause major demographic effects on wild populations. The objective of this study was to estimate the diversity of fauna run over in two highways in northern Rio Grande do Sul. The Roads defined for the study were ERS-331 (T1), which connects the cities of Erechim and Gaurama and RS-420 (T2), which connects the cities of Erechim and Aratiba. The studied region is located within the areas of the Atlantic Forest biome, characterized by a dense rain vegetation and humid subtropical climate. Ten (10) days of sampling were performed by September 2014 to February 2015, totaling 2,880 Km. Only Birds, Mammals and Reptiles were considered in this study. The roadkill rate and the species accumulation curve was calculated. The species richness was estimated based on the use of Jacknife 1 wealth estimator and the species most knocked down was determined from an average of individuals hit by month. The species were classified according to an index of constancy of occurrence. Two hundred and nine individuals of 45 species were found knocked down, being Birds the species with majority of records 57,42% (n=120), followed by Mammals 24,88% (n=52) and Reptiles 17,7% (n=37). The road-kill rates was 0,14 ind./Km/day considering the three taxonomic groups. To Bird we identified 30 species. Eight species of Mammals and seven of Reptiles were identified. Considering all groups the estimated wealth was 67 species (±4,06), among which 46,5 (±3,71) were species of Birds, 11.67 (±1,56) Mammalian species and 8,83 species of reptiles (±1,24). The top five species in running over episodes were: Salvator merianae (n = 24), Didelphis albiventris (n=22), Cerdocyon thous (n=8), Zonotrichia capensis (n=7) and Cavia aperea (n=6). One species is in the list of Rio Grande do Sul's endangered fauna: Leopardus tigrinus, on the "vulnerable" category. The diversity of species ran over, in comparison with estimated species diversity for the region, reinforces the idea that the collisions are directed to some species, probably abundant and who don't avoid the highways. The species with the highest number of accidents coincide largely with the species classified as Constants or Accessory. The road-kill rates showed that at less 50 animals can be found road killed by year in the evaluated roads. The low similarity and the differences between the two roads showed the strong influence the landscape around the roads in the diversity of fauna road-killed. Roads that crossing degraded areas seems impact more animals with generalist habits and roads that crossing preserved areas seems impact animals more exigents about the habitat use. The identification of the species that are most frequently hit and the concerned ecological standards can serve as a tool to make decisions in order to seek alternatives to reduce road kills.